Mass transfer properties of Acacia mangium plantation wood - Tien Manh, Ha; L. Redman, Adam; Pham Van, Chuong; Duy Ngoc, Bui (Maderas. Ciencia y Tecnología, 2021)
This study investigated the mass transfer properties (permeability and mass diffusivity) in the longitudinal, radial and tangential directions of plantation-grown Acacia mangium in Vinh Phuc province, northeast, Vietnam. These properties will be used to complement a conventional drying model in the future. Measurements of gas and liquid permeability were performed using a Porometer (POROLUXTM1000). Mass diffusivity was determined in a constant humidity and temperature chamber using PVC-CHA vaporimeters. Results showed the gas permeability was significant higher than liquid with the descending order of longitudinal, radial, and tangential directions. The permeability anisotropy ratios from the longitudinal to transverse directions of Acacia mangium were much lower than other published species. However, the obvious anisotropy ratios from radial to tangential for both permeability and diffusivity, is one of concerns as they can exacerbate defects during drying. Besides, the high permeability and diffusivity of Acacia mangium compared to some other species reported compounds its relatively fast drying rate.